Optimization of Pedada Mangrove Fruit as a Mangrove Processed Product to Enhance Mangrove Forest Utilization - Ni'matus Sholihah; Fadhil Muhammad Tarmidzi; Jefri Pandu Hidayat; Gevbry Ranti Ramadhani Simamora; Siti Munfarida; Amalia Nur Kumalaningrim (Universitas Lambung Mangkurat, 2024)
Mangrove forests are a unique ecosystem and are important in providing life support for coastal communities. The community group (Kelompok Kariangau Lestari) is a community in Kariangau RT 02 Village that has yet to receive intensive training or socialization regarding the diversification of mangrove derivative products. Mangrove plants are not used properly, so they are only left to grow wild around residential areas. The settlement around the mangrove is used as a tourist attraction, namely Jembatan Panjang Mangrove Kariangau. Still, this tourist attraction is not optimal because the long bridge is the only attraction, and the bridge has been damaged, so there is no longer a source of income for residents. Therefore, this community service activity aims to train community groups to utilize mangrove fruit as a processed food product to attract tourism to the Jembatan Panjang Mangrove Kariangau and increase residents' income. This activity began with observing the condition of the mangrove forest and holding discussions with the local community regarding efforts to increase mangrove forest productivity. In this activity, minimizing processing tools was also carried out to make processed food products and determine the right formulation for processed food products. The evaluation was carried out in two discussions, namely product evaluation, with the result that residents could accept the product as consumers, and activity evaluation, with the result that residents felt this activity was very useful for increasing the current use of mangrove plants.